Search for Nutritional Fitness Traits in a Biological Pest Control Agent Harmonia axyridis Using Comparative Transcriptomics - Zhang, Tingting; He, Yulong; Zeng, Jianyong; Zhang, Lisheng; Zeng, Fanrong; Mao, Jianjun; Zhang, Guocai (Frontiers in Physiology, 2019)
Harmonia axyridis is an important natural predator used in the biological control of insect pests. Vitellogenin (Vg) supplementation to artificial diet can improve fecundity of H. axyridis, however, the effects of Vg on physiology of H. axyridis at the molecular level is unclear. This study investigated the effects of Vg on the physiology (digestive enzyme activities) and transcriptome patterns by feeding H. axyridis adults with treatment (artificial diet with Vg supplement) and control (artificial diet supplemented with bovine serum albumin (BSA). The transcriptome sequencing yielded 43.94 Gb of clean data, and 3,946 differentially expressed genes (DEGs)—including 93 upregulated and 3,853 downregulated genes between the treatment and control. Six DEGs related to development and digestive enzyme were chosen for quantitative real-time PCR (qRT-PCR) to validate the accuracy of the RNA-seq results and confirmed that the transcriptome analysis yielded reliable results. The Vg supplement has increased activities of digestive enzymes and related genes expression in H. axyridis. The transcript level of digestive enzyme genes (apolipoprotein D and phosphoenolpyruvate carboxykinase) were much higher in adults fed on diet supplemented with Vg compared with that of the control.